Hydrothermal Dolomitization on Devonian to Carboniferous Carbonates in Kinta Valley, Perak, Malaysia: A Petrographic Study - Nurul Afiqah Mohammad Zahir; Mirza Arshad Beg; Askury Abdul Kadir (Geological Agency, 2020)
DOI:10.17014/ijog.7.1.25-39Thick Devonian carboniferous carbonates had been deposited in a shallow marine before they were uplifted by granitic intrusion during Triassic. This carbonate platform was selectively dolomitized along N-S oriented deep-seated fault that presented in the carbonate platform. Dolostones are characterized into significant matrix dolomites and several cement dolomites. In petrography point of view, matrix dolomites comprise very fine- to fine-crystalline nonplanar-anhedral dolomite (Dolo-I), fine- to coarse-crystalline nonplanar-anhedral to planar dolomite (Dolo-II), and fine- to medium-crystalline planar- dolomite (Dolo-III). Cement dolomites also consist of medium- to coarse-crystalline planar saddle dolomite (Dolo-IV) which halfway or totally fill disintegration vugs and breaks and coarse- to very coarse-crystalline nonplanar to planar dedolomite (Ded-I). Matrix dolomites predated cement dolomites, later infilled with sepiolite and calcite. The origins of matrix and cement dolomites and other diagenetic minerals are interpreted based on the petrography and isotopic signatures by a previous worker. Dolo-I dolomite was initiated by the early stage of dolomitization with the replacement of calcite by first driving fluids from low to high temperature of magmatic source. While Dolo-II dolomite was formed with slightly modified from Dolo-I and more Mg concentration inputs. Dolo-III dolomite was likely the consequence of hydrothermal fluids causing a brecciation textures as dolomite precipitated rapidly. Subsequently, in a high temperature, the Dolo-III dolomite was formed by precipitation of cement dolomite, hydrothermal fluids as evidenced by highly depleted values of isotopic δ18O. This study intends to provide useful information for understanding the dolomitization processes in alteration of hydrothermal related to Palaeozoic carbonates within Kinta Limestone.